Production of multi‐transgenic pigs tailored for xenotransplantation by using zinc‐finger nucleases and sleeping beauty transposons. (March 2014) - Petersen, Björn; Petkov, Stoyan; Hauschild, Janet; Ahrens, Hellen; Lucas‐Hahn, Andrea; Hassel, Petra; Ziegler, Maren; Hadeler, Klaus‐Gerd; Schwinzer, Reinhard; Niemann, Heiner
<x xml:space="preserve">Abstract</x> Multi‐transgenic pigs are required for prolonging survival of porcine xenografts after transplantation into primate recipients. A homozygous knockout of the alpha1, 3‐galactosyltransferase gene (GGTA‐1, encoding for Gal‐epitopes) is critical for controlling the hyperacute rejection response. Nevertheless, the additional expression of complement regulatory proteins such as CD55 (decay accelerating factor, DAF) on a GGTA‐1 KO background is thought to further improve survival after xenotransplantation. The next hurdle is the acute vascular rejection (AVR), which is primarily caused by endothelial cell activation. Previous experiments had shown that expression of anti‐apoptotic/anti‐inflammatory genes, such as human heme oxygenase‐1 (hHO‐1) or human A20 in pig organs may overcome AVR (1, 2). Adult fibroblasts from previously generated hHO‐1 transgenic pigs were transfected with Zinc‐finger nuclease plasmids directed towards knockout of the GGTA‐1 gene. Transfected cells were selected via a magnetic bead selection approach as previously described (3). GGTA‐1‐KO/hHO‐1 cells were used as donor cells in somatic cell nuclear transfer (SCNT). The first pregnancy was terminated at day 25 of gestation and 11 healthy fetuses were obtained. All fetuses were GGTA‐1‐KO and expressed hHO‐1 at similar levels as the hHO‐1 transgenic cell donors. Next, fetal GGTA‐1‐KO/hHO‐1 cells from one fetus (C6F5) were transfected with a Sleeping Beauty (SB) transposon (kindly provided by Dr. Zoltan Ivics) coding for hCD55. Two positive cell clones were pooled and used as donor cells for SCNT. One pregnancy was terminated on day 25 and four healthy fetuses were obtained which showed the desired GGTA‐1 KO/HO‐1/CD55 genotype. Real‐time PCR detected a 0.9 fold expression of CD55 over the housekeeping gene GAPDH. Compared to human umbilical vein cells (HUVEC), GGTA‐1 KO/HO‐1/CD55 fetal fibroblasts expressed CD55 10–15 fold higher than HUVEC. Two fetuses showed a slightly higher expression of CD55 and are currently used as cell donors for recloning to produce live triple transgenic offspring. To solve the problem of transgene segregation occurring after mating of multitransgenic pigs, we generated two tri‐cistronic SB vectors coding for A20 and CD55 separated by the self‐cleaving peptide E2 site. To select for transfected cells, one vector carried a Tomato‐fluorescence cassette whereas the second conferred puromycin resistance. Red fluorescent/puromycin resistant cells served as donor cells for SCNT. Six healthy fetuses were collected on day 25 of pregnancy; all showed high expression of A20 and CD55 as detected by Real‐time PCR and FACS. One of the fetuses was used as cell donor for recloning. Currently, three pregnancies with A20/CD55 fetuses are going on and will be allowed to go to term. These results show that molecular scissors, including ZFNs and TALENS, and expression vectors such as the Sleeping beauty system are valuable tools to enhance and accelerate the generation of multi‐transgenic pigs for xenotransplantation. References [1] Oropeza M, Petersen B, Carnwath JW et al. Transgenic expression of the human A20 gene in cloned pigs provides protection against apoptotic and inflammatory stimuli. Xenotransplantation. Proc. Nat. Acad. Sci. USA 2009; 16: 522–534. [2] Petersen B, Ramackers W, Lucas‐Hahn A et al. Transgenic expression of human heme oxygenase‐1 in pigs confers resistance against xenograft rejection during ex vivo perfusion of porcine kidneys. Xenotransplantation 2011; in press. [3] Hauschild J, Petersen B, Santiago Y et al. Efficient generation of a biallelic knockout in pigs using zinc‐finger nucleases. Proc. Nat. Acad. Sci. USA. 2011; 108: 12013–12017.